Peningkatan Psychological Well-being Wanita Menopause Melalui Edukasi dan Latihan Self-Acceptance - Yanita Trisetiyaningsih; Azizah, Fajriyati Nur; Hutasoit, Masta (Samodra Ilmu: Lembaga Penelitian, Penerbitan, dan Jurnal Ilmiah, 2025)
The changes experienced during menopause will cause changes in psychological well-being. Based on the results of research conducted by service providers in 2022 on 78 menopausal women, it was found that 73.3% of menopausal women had psychological well-being in the sufficient category, and 9.2% in the poor category. One component of psychological well-being that can be improved in order to improve psychological well-being is related to self-acceptance. Providing education is one way to improve Psychological Well Being and increase self-acceptance for menopausal women. This service activity will be carried out at the Gamping Kidul Ambarketawang Gamping Sleman Yogyakarta Elderly Posyandu. This activity begins with the preparation stage, coordinating and preparing facilities and infrastructure, the implementation stage begins with a pretest, health checks (blood pressure and GDS), and providing education. Health screening and examination activities will be carried out on August 4 and September 1 2023 for climacteric women. The results of the health examination showed that almost 50% of climacteric women had hypertension, and 20% had GDS results that were more than normal. The results of the psychological well-being assessment of climacteric women were carried out on August 4 and September 1 2023. The results showed that the minimum score was 57, the maximum score was 83, and the average score was 69.5.